1990
DOI: 10.2334/josnusd1959.32.281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various root surface treatments on initial clot formation: A scanning electron microscope study.

Abstract: A study was conducted to evaluate using SEM the earliest events of initial blood clot formation on periodontally diseased root surfaces given various treatments. Six teeth with periodontal disease were extracted from six different subjects and were studied in two individual groups. In the first group the root surfaces were divided into three individual treatment areas: (a) intact periodontal ligament, (b) planed, (c) planed and also treated with 1% citric acid. The root surfaces in the second group were likewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
8
0
6
Order By: Relevance
“…In vivo studies have shown the ability of citric acid to provide blood clot stabilization on dental surface 27 (corroborating data of the present study) and to provide linkage between collagen from dental matrix and from periodontal connective tissue. 28,29 The goods results observed in the present study on the adhesion of blood elements over sodium citrate conditioned samples determine the need of additional studies to verify this phenomenon.…”
Section: Discussionsupporting
confidence: 91%
“…In vivo studies have shown the ability of citric acid to provide blood clot stabilization on dental surface 27 (corroborating data of the present study) and to provide linkage between collagen from dental matrix and from periodontal connective tissue. 28,29 The goods results observed in the present study on the adhesion of blood elements over sodium citrate conditioned samples determine the need of additional studies to verify this phenomenon.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the animal studies have histologically shown an increased in new connective tissue attachment, following the use of acid demineralization and FN (2,23,24). Ripamonti et al (25) have shown that this potential may be enhanced by the use of specific attachment glycoproteins and plasma (1,8,11,(28)(29)(30). In spite of the role of FN in promoting periodontal regeneration being evaluated in previous studies, VN and FN-like engineered protein were not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…O uso de ácidos para desmineralizar tecidos duros é bastante antigo, tendo sido amplamente documentado em biomodificação de superfícies de dentina e cemento visando potencializar os processos reparativos em tratamentos de defeitos periodontais (SELVIG et al, 1981;BAL;EREN;BALOS, 1990;HERITIER, 1983;LABAHN et al, 1992;PITARU et al, 1984b;HALS, 1977). O condicionamento ácido de superfícies radiculares tem sido defendido por proporcionar remoção da smear layer resultante da raspagem (REGISTER, 1973;REGISTER;BURDICK, 1975;BLOMLÖF et al, 2000;HERITIER, 1983), descontaminação da superfície (BAL; EREN; BALOS, 1990), liberação de fatores que atuam na cicatrização dos tecidos periodontais (POLSON; PROYE, 1983) e criação de um substrato que privilegia a seleção de células nos eventos de reparação (REGISTER, 1973;REGISTER;BURDICK, 1975;PITARU et al, 1984a;PITARU et al,1984b).…”
Section: Lista De Ilustraçõesunclassified
“…remodelação óssea e eventual substituição óssea (GRAYSON et al, 2015 de dentina e cemento (SELVIG et al, 1981;BAL;EREN;BALOS, 1990;HERITIER, 1983;LABAHN et al, 1992;PITARU et al, 1984a;PITARU et al, 1984b;HALS, 1977), visando potencializar os processos reparativos em tratamentos cirúrgicos periodontais.…”
Section: Revisão De Literaturaunclassified